The impact of touchscreen digital exposure on children’s social development and communication: a systematic review - Misirli, Anastasia; Fotakopoulou, Olga; Dardanou, Maria; Komis, Vassilis (Frontiers in Psychology, 2025)
Touchscreen technologies—ranging from smartphones and tablets to interactive whiteboards and tabletops—are increasingly embedded in the daily lives of young children, shaping how they communicate and interact socially. The present systematic review aims to understand aspects of touchscreen use that support, hinder or explain changes in how young children (ages 1–6) develop social functioning skills such as peer interaction, cooperation, collaboration and communication. Specifically, it explores: (1) the types of touchscreen devices used, (2) their influence on peer interaction, cooperation and collaboration, (3) their effects on communication skills and (4) the developmental, educational, and policy recommendations emerging from the literature. A comprehensive search across Web of Science, ERIC, and Scopus yielded 365 studies, of which 82 met inclusion criteria following PRISMA guidelines. Using a theoretically grounded definition of social functioning and communication, we conducted a content analysis of empirical studies across social sciences, psychology, art and humanities, and computer science. Findings reveal a pervasive presence of touchscreen media in early childhood, with varied impacts shaped by device type, content quality, adult mediation, and contextual factors. This review offers evidence-based insights for educators, parents, and policymakers, emphasizing the value of interactive engagement, teacher training, public education efforts, and community-based approaches in promoting meaningful digital experiences. It stressed the importance of intentional, guided and contextual use of touchscreen technologies in early childhood and family settings. This review offers evidence-based insights for educators, parents, and policymakers, emphasizing the value of interactive engagement, teacher training, public education efforts, and community-based approaches in promoting meaningful digital experiences. It stressed the importance of intentional, guided and contextual use of touchscreen technologies in early childhood and family settings.Systematic review registrationOpen Science Framework https://osf.io/9athz/?view_only=1fa731457d7e48248b7482bca02793f9.